Pedicle streaking: A novel and simple aid in pedicle positioning in free tissue transfer - Aditya Aggarwal; Hardeep Singh; Sanjay Mahendru; Vimalendu Brajesh; Sukhdeep Singh; Ashish Khare; Umang Kothari; Rakesh Kumar Khazanchi (Indian Journal of Plastic Surgery)
Introduction: The pedicle positioning in free tissue transfer is critical to its success. Long thin pedicles are especially prone to this complication where even a slight twist in the perforator can result in flap loss. Pedicles passing through the long tunnels are similarly at risk. Streaking the pedicle with methylene blue is a simple and safe method which increases the safety of free tissue transfer. Materials and Methods: Once the flap is islanded on the pedicle and the vascularity of the flap is confirmed, the pedicle is streaked with methylene blue dye at a distance of 6-7 mm. The streaking starts from the origin of the vessels and continued distally on to the under surface of flap to mark the complete course of the pedicle in alignment. The presence of streaking in some parts and not in rest indicates twist in the pedicle. Observation and Results: Four hundred and sixty five free flaps have been done at our centre in the last 5 years. The overall success rate of free flaps is 95.3% (22 free flap failures). There has not been a single case of pedicle twist leading to flap congestion and failure. Conclusion: This simple and novel method is very reliable for pedicle positioning avoiding any twist necessary for successful free tissue transfer.